Ethics of the Body and Sexuation: Plasticity and Flow in the Subject of Postfeminism - Balza, Isabel (Revista Estudos Feministas, 2011)
The sexual position analyzed by Jacques Lacan in his Seminar XX (1973) shows thestructure of normative heterosexuality: a binary order of the sexed bodies assuming two exclusivemodes of sexuality. This sexual economy encodes the equation having/being the phallus. Facingthe lacanian body ethics, feminist thought has posed other sexual positions. I propose to analyzeMonique Wittig’s radical feminism, interpreting The Lesbian Body (1973) as a critical mode ofbeing the lacanian phallus, and to examine Judith Butler’s critique in her discussion of the lesbianphallus (Bodies that Matter, 1993). Butler breaks the exclusive binary logic, opening the possibilityfor a sexed body to be and to have the phallus simultaneously. Lastly, I will examine the proposalof dildoes that Beatriz Preciado raises in her Manifesto contra-sexual (2002).